Paradoxical Decision-Making: A Framework for Understanding Cognition in Parkinson's Disease - Perugini, Alessandra (Trends Neurosci, 2018)
People with Parkinson’s disease (PD) show impaired decision-making when sensory and memory information must be combined. This recently identified impairment results from an inability to accumulate the proper amount of information needed to make a decision and appears independent of dopamine tone and reinforcement learning mechanisms. Although considerable work focuses on PD and decisions involving risk and reward, in this Opinion piece, we propose that the emerging findings in perceptual decision-making highlight the multisystem nature of PD and that unraveling the neuronal circuits underlying perceptual decision-making impairment may help understand other cognitive impairments in people with PD. We also discuss how a decision-making framework could be extended to gain insights into mechanisms of motor impairments in PD.